Measurable bundles of *-homomorphisms C*-algebras - Ganiev, Inomjon; Kudaybergenov, Karimbergen (Faculty of Engineering, 2012)
In the present paper we study ¤-homomorphisms on C¤-algebras over a ring of measurable functions L0: In particular, we give representation ¤-homomorphisms on C¤-algebras over L0 as measurable bundles of ¤-homomorphisms on complex C¤-algebras.